MEAMfit: A reference-free modified embedded atom method (RF-MEAM) energy and force-fitting code - Duff, Andrew Ian (Computer physics communications, 2016)
MEAMfit v1.02. Changes: various bug fixes; speed of single-shot energy and force calculations (not optimization) increased by ×10; elements up to Cn (Z=112) now correctly read from vasprun.xml files; EAM fits now produce Camelion output files; changed max number of vasprun.xml files to 10,000 (an unnecessary lower limit of 10 was allowed in the previous version). Program title: MEAMfit Catalogue identifier: AEWY_v1_1 Program summary URL:http://cpc.cs.qub.ac.uk/summaries/AEWY_v1_1.html Program obtainable from: CPC Program Library, Queen’s University, Belfast, N. Ireland Licensing provisions: BSD 2-Clause License No. of lines in distributed program, including test data, etc.: 5202334 No. of bytes in distributed program, including test data, etc.: 66637698 Distribution format: tar.gz Programming language: Fortran. Computer: Linux based workstations. Operating system: Linux. RAM: 120 MB Classification: 16.1. Catalogue identifier of previous version: AEWY_v1_0 Journal reference of previous version: Comput. Phys. Comm. 196 (2015) 439 External routines: TOMS611 Unconstrained Minimization [1] included in the MEAMfit code. Does the new version supersede the previous version?: Yes Nature of problem: Fitting embedded atom method (EAM) and reference-free modified embedded atom method (RF-MEAM) potentials [2–3] to energies and forces produced by VASP [4–7]. Solution method: A computer program is presented which uses a conjugate-gradient minimizer paired with a genetic algorithm to fit EAM and RF-MEAM potentials to energies and/or atomic forces read directly from VASP output files. Potentials produced by the code are directly usable with the LAMMPS [8] or Camelion [9] molecular-dynamics packages. Reasons for new version: Bugs fixed; improvements made. Summary of revisions: Various bug fixes; speed of single-shot energy and force calculations (not optimization) increased by ×10; elements up to Cn (Z=112) now correctly read from vasprun.xml files; EAM fits now produce Camelion output files; changed max number of vasprun.xml files to 10,000 (an unnecessary lower limit of 10 was allowed in the previous version). Additional comments: User manual provided. !!! The distribution file for this program is over 65 MB and therefore is not delivered directly when download or Email is requested. Instead a html file giving details of how the program can be obtained is sent. !!! Running time: The run-time depends on the required level of accuracy of the final potential. For an EAM potential fit to 670 energies, a few hours on a single core is usually sufficient to produce a potential with R=12%–13% (see Equation. 9 in main-text for definition). To ensure a maximally optimized potential however (R=12%), a run-time of 24 h is recommended. To optimize a RF-MEAM potential, a further 24 h should be allowed. One will already find an improvement over the EAM using just a single core, however to ensure a maximally optimized potential, one should run several instances of MEAMfit in parallel. References:[1]J. E. Dennis, D. Gay and R. E. Welsch, ACM Trans. on Math. Soft., 7 (1981) 348–368.[2]M. I. Baskes, Materials Science and Engineering A, 261 (1999), 165.[3]M. Timonova and B. J. Thijsse, Modelling Simul. Mater. Sci. Eng., 19 (2011) 015003[4]G. Kresse, J. Hafner, Phys. Rev. B 47 (1993) 558.[5]G. Kresse, J. Hafner, Phys. Rev. B 49 (1994) 14251.[6]G. Kresse, J. Furthmüller, Comput. Mat. Sci. 6 (1996) 15.[7]G. Kresse, J. Furthmüller, Phys. Rev. B 54 (1996) 11169.[8]S. Plimpton, J. Comp. Phys. 117 (1995)[9]http//://tinyurl.com/camelion11-53